Pemanfaatan Pool Serum sebagai Bahan Kontrol Ketelitian Pemeriksaan Glukosa Darah - muhammad muslim; yayuk kustiningsih; endah yanuarti (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2015)
Efforts to efficiency in the implementation of the medical laboratory's internal quality control is done with the use of control serum pool. Pool control serum is a material made from leftover serum of patients who generally discarded because it is not used anymore .. The purpose of the study to determine the accuracy of the quality of the pool serum as compared with the control materials for the plant control serum glucose in improving internal quality control. Type analytic survey research with comparative approach. Analysis of data using the value of CV (coefficient of variation) and the Wilcoxon test. The results showed a decrease in serum pool of blood glucose levels after 30 days of storage by 4.7%. Based on a statistical test serum taken with the pool serum obtained significance value of 0.000 where this value is less than the value of α = 0.05, which means that there is a difference between serum taken with the pool serum. In the control serum before and after storage decreased blood glucose levels of 4.5% and is based on statistical test obtained significance value of 0.073 where the value is more than the value of α = 0.05, so there is no difference between the control serum before and after storage. Based on the calculation, the value of CV (coefficient of variation) of 5.4% serum pool and a CV (coefficient of variation) control serum by 11.6%. Accuracy pool serum and serum control exceeds the limits CV (coefficient of variation) a maximum of 5%. It is suggested further research on how long endurance pool serum as a control.